Carcinoma of the Papilla of Vater after Diversion Operation for Pancreaticobiliary Maljunction - Takahiro Yamanaka; Kenichiro Araki; Norihiro Ishii; Mariko Tsukagoshi; Takamichi Igarashi; Akira Watanabe; Norio Kubo; Hiroyuki Kuwano; Ken Shirabe (Case Reports in Gastroenterology, 2017)
Pancreaticobiliary maljunction (PBM) is a congenital malformation that is associated with biliary cancer development. When patients are diagnosed with PBM, a diversion operation is recommended. Although a risk remains for developing residual bile duct carcinoma following diversion, the development of a carcinoma of the ampulla of Vater after a diversion operation for PBM is rare. We present a treated case of carcinoma of the ampulla of Vater after a diversion operation for PBM. A 65-year-old woman presented with abdominal pain. She had undergone extrahepatic bile duct resection and cholecystectomy 2 years 9 months previously for the treatment of type Ic PBM according to the Todani classification. At the current admission for evaluation of the abdominal pain, computed tomography and magnetic resonance imaging showed only dilation of the main pancreatic duct. However, gastrointestinal endoscopy showed a tumor at the papilla of Vater, and biopsy revealed adenocarcinoma of the papilla of Vater. We performed pylorus-preserving pancreaticoduodenectomy, and the pathological diagnosis was moderately differentiated tubular adenocarcinoma of the papilla of Vater with no metastasis to the lymph nodes. The patient remained in good health for 3 years postoperatively. Carcinoma of the papilla of Vater after a diversion operation for PBM is rare. In this case, a diagnosis could not be made by computed tomography or magnetic resonance imaging; the definitive diagnosis was obtained with gastrointestinal endoscopy. Careful postoperative follow-up with gastrointestinal endoscopy in addition to imaging examination may be needed after a diversion operation for PBM.